PERAN MODERASI LITERASI KEUANGAN DALAM KEUANGAN PERILAKU: STUDI PADA INVESTOR MUDA KOTA SORONG - Ignatz Novrian Fayliencent; Ferdinando Solissa; Margaretha Turot; Putu Anggreyani Widya Astuty; Iyonna Jermina Salakay; Angeli Prisca Pitaloka (LPPM STIE YKPN Yogyakarta, 2026)
The rapid growth of financial technology (fintech) has expanded financial inclusion while simultaneously increasing behavioral risks in investment decision-making, particularly among young investors. This study examines the effect of behavioral biases—overconfidence bias, herding bias, and mental accounting—on investment decisions of young investors in Sorong City, and investigates the moderating role of financial literacy while considering gender differences. Using a quantitative approach, data were collected from 216 respondents aged 19–34 years through structured questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results reveal that overconfidence bias and mental accounting have a positive and significant effect on investment decisions for both male and female investors, while herding bias significantly influences investment decisions only among male investors. Furthermore, financial literacy does not moderate the relationship between behavioral biases and investment decisions across genders. These findings indicate that higher financial literacy does not necessarily mitigate behavioral biases in a fintech-driven investment environment. This study contributes to behavioral finance literature by providing empirical evidence from a developing country context and offers practical implications for policymakers and fintech providers in designing more effective financial education programs and investor protection mechanisms targeting young investors.